2005
DOI: 10.1007/s00167-005-0677-y
|View full text |Cite
|
Sign up to set email alerts
|

Femoral avulsion fracture of the posterior cruciate ligament in association with a rupture of the popliteal artery in a 9-year-old boy: a case report

Abstract: Ruptures of the posterior cruciate ligament (PCL) and especially proximal bony avulsion fractures in children are very rare. This in combination with a rupture of the popliteal artery is extremely rare. Thus, an exact incidence is not available from the literature. Overall, these injuries are severe and often lead to chronic knee instability. We report a case of a 9-year-old boy who suffered a traumatic displacement of the left knee with a rupture of the popliteal artery. Prior to transfer to our department, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
(39 reference statements)
0
30
0
Order By: Relevance
“…Furthermore, the relative weakness of the physis and bone in comparison to the ligament more commonly results in osteochondral avulsions rather than ligamentous substance tears as seen in adults [2,6,9,13,19,21,22,[26][27][28]. However, femoral avulsions of the PCL are reported more frequently than those of the tibial insertion site in children [10,12,13,19,21,25,26,28] (Table 1), and clinicians may not be as aware of the specific history, physical examination, and radiographic findings of these tibial-sided injuries as compared with those of the femur such as the need for specific imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relative weakness of the physis and bone in comparison to the ligament more commonly results in osteochondral avulsions rather than ligamentous substance tears as seen in adults [2,6,9,13,19,21,22,[26][27][28]. However, femoral avulsions of the PCL are reported more frequently than those of the tibial insertion site in children [10,12,13,19,21,25,26,28] (Table 1), and clinicians may not be as aware of the specific history, physical examination, and radiographic findings of these tibial-sided injuries as compared with those of the femur such as the need for specific imaging.…”
Section: Introductionmentioning
confidence: 99%
“…After a comprehensive search, we found 11 cases of PCL avulsion fractures of femoral origin in adolescents in the literature [6,14,15,21,27]. In contrast, only four cases of PCL avulsions of femoral origin have been reported in adults [8,17,22,23] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the five patients had involvement of only the lateral cortex of the medial femoral condyle and the other two had osteochondral avulsions (Table 1). Damages from PCL avulsions include medial collateral ligament avulsion [22,23], ACL avulsion [22,23], capsule rupture [8], and possible vascular or nerve injury [14], especially in a dislocated knee. Hesse et al [14] reported a femoral avulsion fracture of the PCL was associated with rupture of the popliteal artery in a 9-year-old boy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different degrees of PCL injury result in varied laxity of the PCL, and the degree of laxity is an important clinical reference for treatment choices for PCL injury patients (Adachi et al, 2003;Doberstein et al, 1997;Logan et al, 2004;Wang et al, 2002;Hesse et al, 2006). To the authors' knowledge, only a few studies have quantified tibiofemoral laxity in knees with different PCL injuries.…”
Section: Introductionmentioning
confidence: 95%